The Effect of Adding Types of Agricultural Residues on the Concrete Behaviour - Abdul Kareem, Wael Shahadha; Mijwal Aljumaily, Hadi Salih; Nsaif Abbas, Mohammed (International Journal of Scientific Research in Civil Engineering, 2019)
Numerous of renowned conglomerates declared every year a new brands of classical chemical admixtures, but there was no one disclosed a new brand manufactured from a food waste, on another hand, due to the proliferation of wastes resulting from the foodstuff which is included within the environmental pollution framework. So this issue-study is to parade the ability of utilizing pomegranate leaves powder (PLP) as an admixture to magnify the compressive strength of Ordinary Portland Concrete (OPC), and to emerge the effect of these peels on the behavior and the properties of concrete. The ratio of (PLP/cement) was ranging between 0-1.0% by weight with mix proportion of (1:2:4) (cement:sand:gravel) by volume and a constant water to cement ratio (W/C) of 0.45. An evolve rate of 14.4% in concrete compressive strength was observed with increasing the ratio of PLP admixtures to 0.15%. Thus, the pomegranate leaves deem to be superb and efficient.
Keywords: Ordinary Portland Concrete; Water to Cement Ratio; Pomegranate Leaves Powder; Ordinary Portland Cement